Comparative description and taxonomic affinity of 3.7-million-year-old hominin mandibles from Woranso-Mille (Ethiopia). Issue 173 (December 2022) - Haile-Selassie, Yohannes; Saylor, Beverly Z.; Alene, Mulugeta; Deino, Alan; Gibert, Luis; Schwartz, Gary T.
Abstract: Fossil discoveries of early Australopithecus species from Woranso-Mille have played a significant role in improving our understanding of mid-Pliocene hominin evolution and diversity. Here, we describe two mandibles with dentitions, recovered from sediments immediately above a tuff radiometrically dated to 3.76 ± 0.02 Ma, and assess their taxonomic affinity. The two mandibles (MSD-VP-5/16 and MSD-VP-5/50) show morphological similarities with both Australopithecus anamensis and Australopithecus afarensis . Some of the unique features that distinguish Au. anamensis from Au. afarensis are present in the mandibles, which also share a few derived features with Au. afarensis . Their retention of more Kanapoi Au. anamensis -like traits, compared to the fewer derived features they share with Au. afarensis, and the presence of Au. anamensis at Woranso-Mille in 3.8-million-year-old deposits, lends support to their assignment to Au. anamensis . However, it is equally arguable that the few derived dentognathic features they share with Au. afarensis could be taxonomically more significant, making it difficult to conclusively assign these specimens to either species. Regardless of which species they are assigned to, the mosaic nature of the dentognathic morphology and geological age of the two mandibles lends further support to the hypothesized ancestor–descendant relationship between Au. anamensis and Au. afarensis . However, there is now limited fossil evidence indicating that these two species may have overlapped in time. Hence, the last appearance of Au. anamensis and first appearance of Au. afarensis are currently unknown. Recovery of Australopithecus fossils from 4.1 to 3.8 Ma is critical to further address the timing of these events.